Inspecting sound sources in an orifice-jet flow using Lagrangian coherent structures. (25th November 2016) - Nair, Vineeth; Alenius, Emma; Boij, Susann; Efraimsson, Gunilla
Highlights: Compressible implicit LES simulations of an orifice-jet flow are performed. A novel method (bFTLE + DMD) is proposed to identify vortex structures. bFTLE fields of DMD resolved flow are computed at the peak DMD frequencies. Comparing the pressure and DMD spectra, structures present at sound generation are identified. The method resolves shear layer better than the vortex detection criterion based on λ 2 . Abstract: A novel method is proposed to identify flow structures responsible for sound generation in confined flow past an inhibitor. Velocity fields obtained using Large Eddy Simulations (LES) are post-processed to compute the Finite Time Lyapunov Exponent (FTLE) field, the ridges of which in backward time represent an approximation to Lagrangian Coherent Structures (LCS), the structures that organize transport in the flow field. The flow-field is first decomposed using dynamic mode decomposition (DMD), and the organizing centers or vortices at the significant DMD frequencies are extracted. The results are then compared with the λ 2 criterion. Features such as shear layer roll-up and development of secondary instabilities are more clearly visible in the FTLE field than with the λ 2 criterion.